Modified intramuscular adipose tissue content as a feasible surrogate marker for malnutrition in gastrointestinal cancer. Issue 5 (May 2021) - Kusunoki, Yukina; Okugawa, Yoshinaga; Toiyama, Yuji; Kusunoki, Kurando; Ichikawa, Takashi; Ide, Shozo; Shimura, Tadanobu; Kitajima, Takahito; Imaoka, Hiroki; Fujikawa, Hiroyuki; Yasuda, Hiromi; Yokoe, Takeshi; et al.
Summary: Background & aims: Myosteatosis is gathering attention as a feasible indicator for sarcopenia and increased risk of morbidity. However, the prognostic value of intramuscular adipose tissue content (IMAC) as an assessment method for myosteatosis remains controversial. The objectives of this study are to compare the prognostic value of intramuscular adipose tissue content (IMAC) with our newly-developed modified IMAC (mIMAC), and to assess the clinical significance of mIMAC in colorectal cancer (CRC) and gastric cancer (GC). Methods: We evaluated 892 patients with CRC or GC, and assessed preoperative IMAC and mIMAC to compare their prognostic and predictive values for postoperative infectious complications in both cohorts. Results: Both preoperative IMAC and mIMAC were sex- and disease-dependent, and positively or negatively correlated with age in CRC and GC patients (IMAC: CRC: r = 0.33, P < 0.0001; GC: r = 0.304, P < 0.0001; mIMAC: CRC: r = −0.364, P < 0.0001; GC: r = −0.263, P < 0.0001). In contrast to IMAC, lower preoperative mIMAC was significantly associated with disease-development factors, and was an independent prognostic factor for both overall survival (OS) and disease-free survival (DFS) in both CRC (OS: hazard ratio (HR): 1.95, 95% confidence interval (CI): 1.25–3.03, p = 0.003; DFS: HR: 1.93, 95% CI: 1.22–3.04, p = 0.005) and GC patients (OS: HR: 2.11, 95% CI: 1.22–3.68, P = 0.008; DFS: HR: 2.03, 95% CI: 1.18–3.5, P = 0.011). Patients with postoperative remote infections had a poorer prognosis compared with those without in both cohorts (CRC: HR: 2.67, 95% CI: 1.46–4.89, P = 0.002; GC: HR: 3.01, 95% CI: 1.47–6.19, P = 0.003), and low mIMAC was an independent risk factor for postoperative remote infection in both cancers (CRC: odds ratio (OR): 2.56, 95% CI: 1.06–6.23, P = 0.038; GC: OR: 2.8, 95% CI: 1.03–7.58, P = 0.043). Finally, we assessed the correlation between IMAC or mIMAC and the representative frailty markers body mass index (BMI), serum albumin, and prognostic nutritional index (PNI). We found a positive correlation between preoperative mIMAC and all of these markers in both cohorts (CRC: BMI: r = 0.193, P < 0.0001; serum albumin: r = 0.42, P < 0.0001; PNI: r = 0.39, P < 0.0001; GC: BMI: r = 0.22, P < 0.0001; serum albumin: r = 0.212, P < 0.0001; PNI: r = 0.287, P < 0.0001). Conclusions: Preoperative mIMAC could be useful for perioperative and postoperative management in CRC and GC. Highlights: Myosteatosis is a feasible indicator for sarcopenia and increased risk of morbidity. We developed a new formula as an indicator of myosteatosis. We identified that mIMAC was a powerful indicator of host nutritional status. MIMAC was a predictive marker for short- and long-term outcomes in GI cancer patients.